2010
DOI: 10.1161/circresaha.110.226977
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the Brain (Pro)renin Receptor in Cardiovascular Homeostasis

Abstract: Key Words: (pro)renin receptor Ⅲ supraoptic nucleus Ⅲ cardiovascular homeostasis Ⅲ mean arterial pressure E vidence demonstrates that the renin-angiotensin system (RAS) is intrinsic to the brain and has an integral role in the neural control of cardiovascular functions. 1,2 Despite this, there is ongoing debate about the existence of an intrinsic brain RAS. 1,3 Skeptics have argued that brain levels of renin are too low to have any impact on angiotensin II formation and hence its actions. [3][4][5] In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
85
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(88 citation statements)
references
References 11 publications
2
85
1
Order By: Relevance
“…(P)RR was colocalized with vasopressin in the paraventricular and supraoptic neurons of hypothalamus (Takahashi et al 2010a). Shan et al (2010) showed that (P)RR overexpression in the supraoptic nucleus stimulated vasopressin secretion and chronic knockdown of (P)RR decreased it in rats, suggesting that (P)RR plays a role in vasopressin secretion in the hypothalamus. Hypothalamic (P)RR may therefore modulate the vasopressin secretion against dehydration.…”
Section: Discussionmentioning
confidence: 97%
“…(P)RR was colocalized with vasopressin in the paraventricular and supraoptic neurons of hypothalamus (Takahashi et al 2010a). Shan et al (2010) showed that (P)RR overexpression in the supraoptic nucleus stimulated vasopressin secretion and chronic knockdown of (P)RR decreased it in rats, suggesting that (P)RR plays a role in vasopressin secretion in the hypothalamus. Hypothalamic (P)RR may therefore modulate the vasopressin secretion against dehydration.…”
Section: Discussionmentioning
confidence: 97%
“…The importance of the brain PRR in cardiovascular control is further strengthened by the observation that increased PRR expression in brain cardiovascular control areas altered body fluid homeostasis (38) and genetic knockdown of the PRR induced long-term depressor effects in hypertensive animals (21,22,38). However, the detailed mechanism underlying the role of brain PRR on blood pressure regulation is not well understood.…”
Section: To Our Best Knowledge This Study Is the First To Investigatmentioning
confidence: 99%
“…Chronic overexpression of this receptor in the SON alters body fluid homeostasis in normotensive rats, while genetic knockdown of the expression of SON PRR significantly attenuated the age-dependent blood pressure increase in the SHR (38), indicating hypothalamic PRR plays a critical role in the control of blood pressure. PRR is also highly expressed in the hypothalamic paraventricular nucleus (PVN) (7,38). The PVN is one of the most important brain areas controlling sympathetic outflow.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…(P)RR is expressed in the adult brain, where it plays a role in the neural control of cardiovascular functions, regulation of Erk1/2 signaling, and neuron differentiation (5,32). The possibility that (P)RR may be important for brain development is supported by the findings that Xenopus embryos injected with (P)RR antisense morpholino oligonucleotides have small head size (25).…”
Section: Discussionmentioning
confidence: 99%